Professional repositioning during times of institutional change: The case of tax practitioners and changing moral boundaries - Radcliffe, Vaughan S.; Spence, Crawford; Stein, Mitchell; Wilkinson, Brett (Accounting, Organizations and Society, 2018)
Recent work has called for more research to be carried out exploring how professional projects develop in conjunction with wider processes of institutional change. We respond to these calls here by analysing the way in which tax professionals have responded to a major disruption at the field level. The Organization for Economic Co-operation and Development's action plan on Base Erosion and Profit Shifting has proposed far reaching reforms in an attempt to bring corporate tax practice into line with changing moral boundaries in society. Through a combination of documentary analysis, participant observation and qualitative interviews, this paper shows how tax professionals negotiate changing moral imperatives. In doing so, the paper enhances our understanding of tax practice and contributes to extant literature on professionalization and institutional change in three principal ways. Firstly, we show how exogenous field-level changes afford professional groups opportunities for strategic repositioning. Secondly, we illustrate how different professional factions are differentially affected by processes of institutional change, distinguishing between in-house tax professionals and those working in public practice. Thirdly, we demonstrate how this strategic repositioning is made possible by the skillful deployment of the technical-cognitive resources of professional groups.